HISTORICAL NARRATIVE AS THE FOUNDATION OF STRATEGIC CULTURE: A CASE STUDY OF THE REPUBLIC OF SERBIA - Kesić, Dušan (National interest, 2026)
This paper underscores the central importance of historical narrative as the foundation of strategic culture. Anchored in the assumptions of moderate constructivism, the concept of strategic culture places at the center of analysis the question of the causal relationship between ideational factors (i.e., identity, norms, values, and ideas) and national security policy. By situating strategic culture within the constructivist research program, it becomes possible to treat historical narrative as its ideational foundation. Accordingly, the starting hypothesis of this paper is based on the assumption that historical narrative constitutes the ideational foundation of the strategic culture of the Republic of Serbia. In other words, the historical narrative encompasses key ideas, beliefs, values, and norms relevant to national security policy.The hypothesis is tested through a case study of Serbia’s strategic culture, based on an analysis of the institutionalized historical narrative. Using qualitative content analysis, history textbooks are examined as the referential basis of the historical narrative. The primary objective of the research is to identify the ideational factors of the strategic culture of the Republic of Serbia across four analytical dimensions: identity, values, norms, and worldview. The temporal scope of the research covers the period from the 1990s to the present.The analysis of the historical narrative enables the deduction and identification of ideational factors that underpin the core dimensions of the strategic culture of the Republic of Serbia. The identified ideational factors demonstrate mutual coherence, with the dimension of identity emerging as the cornerstone of the remaining analytical dimensions and of the strategic culture of the Republic of Serbia as a whole. Specifically, the identified key national and state interests, legitimate methods for their realization, and perceptions of other states and nations are deeply rooted in national self-understanding and in the characteristics of the Serbian national character.
Keywords: strategic culture; constructivism; historical narrative; national security policy; the Republic of Serbia